Microspot sensing based on surface-enhanced fluorescence from nanosculptured thin films - Karabchevsky, Alina (2014)
Nanosculptured thin films (STF) are prepared by the oblique angle deposition technique and take different forms of nano columnar structures. Varieties of STFs were investigated to find the optimum structure for biosensing based on the surface enhanced fluorescence. A comparative study was carried out with STFs containing the nanocolumnar structures that differ in their shape, height (h), and tilt angle with respect to the surface (α), thickness (d), and arrangement. The greatest enhancement of the fluorescent signal was found for Ag-based STFs on Si(100), giving an enhancement factor of ×71, where h=400  nm, d=75  nm, and α=23° relative to Ag closed film using fluorescent dye Rhodamine 123. We immobilized the fluorescent receptor to the thiol self-assembly monolayer on Ag-based STF and Ag dense film to demonstrate the applications of STFs for specific biosensing. Upon excitation of the fluorophore by an Hg light source, a CCD camera with controlled exposure time would detect the pattern of fluorescent receptor Anti-Rabbit IgG on the surfaces. A specially designed optical fiber housing attached to the microscope allowed quantitative measurement of the fluorescence spectrum on a microspot parallel to the image grab.